Assessment of neurocognitive deficits in people living with HIV in Sub Saharan Africa: A systematic review. (10th December 2019) - Nyamayaro, Primrose; Chibanda, Dixon; Robbins, Reuben N.; Hakim, James; Gouse, Hetta
Abstract: Objective: People living with HIV (PLWH) are at risk for HIV-Associated Neurocognitive Disorders (HAND)/Neurocognitive Impairment (NCI). HIV prevalence in Sub-Saharan Africa (SSA) is high, but neuropsychological screening and testing for NCI among HIV-infected individuals is not done frequently. This systematic review aims to establish how NCI among HIV-infected individuals is being assessed in SSA, if and how the tests are adapted, if norms exist and identify personnel who administer them. Method: We searched PubMed, Medline, EBSCO, PsycINFO, and Web of Science. Two reviewers screened the articles for inclusion and risk of bias. We included studies from SSA with a comprehensive neuropsychological assessment battery. Results: We retrieved 212 articles and 23 articles met inclusion criteria. The most commonly used tests were the Color Trails Test 1, Color Trails Test 2, and the WAIS III Digit Symbol Test. Some tests were translated into French (Cameroon), Luganda (Uganda), Chichewa (Malawi), isiXhosa (South Africa), and Afrikaans (South Africa). Some verbal learning tests were adapted to reflect culturally appropriate language. Test administrators were either non-specialized personnel supervised by clinical neuropsychologists or clinical psychologists. Conclusion: Overall, the tests used are similar to the tests being used globally to assess NCI among HIV-infected individuals and there is a general consistency across countries. However, there is generally a lack of norms for the tests and the process of adaptation is not always well described. Future research should establish whether these tests measure neuropsychological constructs as successfully as they do in western populations where the tests were developed.